If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 5y) + (-8x + -9y) = 0 Remove parenthesis around (7x + 5y) 7x + 5y + (-8x + -9y) = 0 Remove parenthesis around (-8x + -9y) 7x + 5y + -8x + -9y = 0 Reorder the terms: 7x + -8x + 5y + -9y = 0 Combine like terms: 7x + -8x = -1x -1x + 5y + -9y = 0 Combine like terms: 5y + -9y = -4y -1x + -4y = 0 Solving -1x + -4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. -1x + -4y + 4y = 0 + 4y Combine like terms: -4y + 4y = 0 -1x + 0 = 0 + 4y -1x = 0 + 4y Remove the zero: -1x = 4y Divide each side by '-1'. x = -4y Simplifying x = -4y
| 9y^4(4y^2-8y+6)= | | -13x=221 | | y^2-17y+72=0 | | y^2-15y+56=0 | | -3(z-4)= | | -3z-2z= | | x-7.9=-5.5 | | 9x-5=76 | | 8x+24=48 | | 6x+12=60 | | 0=-8y+21 | | -2x^2+6x+9=0 | | a^4b+a^2b^3= | | 0.05x-0.6=5.3 | | 12=2x+2x+2x | | 14=2x+2y+4z | | w=m-5L | | 2-6x=7x+2 | | 20g^2=16g | | 8+3(4x-4)=5-4(2x+1) | | X=6+-1y+-1z | | -24c^2=36 | | 3x-y=-3 | | (x+2)(x-1)=40 | | 3m=2 | | 6d=0 | | 3x+12=7x-16 | | 3x+12=7x-17 | | 4x-6x+3=2x+11 | | 5x+4=3x-2x+4x | | y=2.2 | | 13+5=6E+(-4)+(-5) |